Cinema of Discontent : Representations of Japan's High-Speed Growth. - Sasaki, Tomoyuki (SUNY Series, Horizons of Cinema Ser., 2022)
Uses popular films to reveal the tensions generated during Japan's postwar "economic miracle," challenging the prevailing view that it was a story of great national success.